Amean S. Ghazi The Effect Of Curvature Rate On The Received Power in the Parabolic Reflector - Amean Ghazi (University of Thi-Qar Journal of Science, 2019)
is paper we study the effect of curvature rate on the generated electric field at the focus point if the frequency and diameter are constants .We assume that the incident electromagnetic waves distributed uniformly on each point of the reflector surface ;hence we can imagine that this reflector has uniform surface charge ,and this body will generate an electric field on all points in front of it (including the focus point) . This field can be obtained by us incoulomb’s law .The derived expression for electric field show that X and Y components will vanish and the electric field has a Z-component only (axis of symmetry) .We draw the resultant electric field as a function of (F/D) ratio at constant antenna diameter .The obtained result showed that the electric field will increase as (F/D) ratio decrease, and decrease as (F/D) ratio increase if antenna diameter is constant .There  is some fluctuations in the values of electric field when antenna diameter is small ,and this fluctuations will decrease as antenna diameter increase at constant (F/D) ratio.